Comparison between noninvasive mechanical ventilation and standard oxygen therapy in children up to 3 years old with respiratory failure after extubation: a pilot prospective randomized clinical study - Fioretto, Jose R. [UNESP]; Ribeiro, Cristiane F. [UNESP]; Carpi, Mario F. [UNESP]; Bonatto, Rossano C. [UNESP]; Moraes, Marcos A. [UNESP]; Fioretto, Eduardo B.; Fagundes, Djalma J. (Lippincott Williams &wilkins, 2015)
Objectives: The effectiveness of noninvasive positive-pressure ventilation in preventing reintubation due to respiratory failure in children remains uncertain. A pilot study was designed to evaluate the frequency of extubation failure, develop a randomization approach, and analyze the feasibility of a powered randomized trial to compare noninvasive positive-pressure ventilation and standard oxygen therapy post extubation for preventing reintubation within 48 hours in children with respiratory failure.Design: Prospective pilot study.Setting: PICU at a university-affiliated hospital.Patients: Children aged between 28 days and 3 years undergoing invasive mechanical ventilation for greater than or equal to 48 hours with respiratory failure after programmed extubation.Interventions: Patients were prospectively enrolled and randomly assigned into noninvasive positive-pressure ventilation group and inhaled oxygen group after programmed extubation from May 2012 to May 2013.Measurements and Main Results: Length of stay in PICU and hospital, oxygenation index, blood gas before and after tracheal extubation, failure and reason for tracheal extubation, complications, mechanical ventilation variables before tracheal extubation, arterial blood gas, and respiratory and heart rates before and 1 hour after tracheal extubation were analyzed. One hundred eight patients were included (noninvasive positive-pressure ventilation group, n = 55 and inhaled oxygen group, n = 53), with 66 exclusions. Groups did not significantly differ for gender, age, disease severity, Pediatric Risk of Mortality at admission, tracheal intubation, and mechanical ventilation indications. There was no statistically significant difference in reintubation rate (noninvasive positive-pressure ventilation group, 9.1%; inhaled oxygen group, 11.3%; p > 0.05) and length of stay (days) in PICU (noninvasive positive-pressure ventilation group, 3 [116]; inhaled oxygen group, 2 [1-25]; p > 0.05) or hospital (noninvasive positive-pressure ventilation group, 19 [7-141]; inhaled oxygen group, 17 [8-80]).Conclusions: The study indicates that a larger randomized trial comparing noninvasive positive-pressure ventilation and standard oxygen therapy in children with respiratory failure is feasible, providing a basis for a future trial in this setting. No differences were seen between groups. The number of excluded patients was high.
Keywords: Children; Extubation; Intubation; Noninvasive mechanical ventilation; Respiratory failure